2022
DOI: 10.1021/acsearthspacechem.2c00057
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Isothermal Stage Pyrolysis of the Chang 73 Shale Oil Reservoirs, Ordos Basin: Implications for Oil Occurrence States and In Situ Conversion Exploitation

Abstract: Understanding the content, component features, and controlling factors of hydrocarbons in different occurrence states is a key element in assessing the resource potential, mobility, and engineering exploitability of shale oil. X-ray diffraction, bulk geochemistry, multi-isothermal stage pyrolysis experiments, and total hydrocarbon chromatographic analyses were performed on a set of muddy siltstone (MS), fine sandstone (FS), dark mudstone (DM), and black shale (BS) from the Chang 73 subsection in the Huachi are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In general, petroleum with a higher API gravity contains more light components. Studies employing TD‐GC–MS/FID have demonstrated that shale products evaporated at relatively lower temperatures have significantly fewer carbon atoms and lower molecular weight (Abrams et al, 2017; Guo et al, 2022; Jiang, Li, et al, 2016; Romero‐Sarmiento, Euzen, et al, 2016). To assess the proportions of different pyrolysis fractions in the shale samples, Oil‐1, Oil‐2, Oil‐3, and Oil‐4 obtained through multi‐step programmed pyrolysis were normalized and expressed as percentages (P Oil‐1 , P Oil‐2 , P Oil‐3 , and P Oil‐4 ) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, petroleum with a higher API gravity contains more light components. Studies employing TD‐GC–MS/FID have demonstrated that shale products evaporated at relatively lower temperatures have significantly fewer carbon atoms and lower molecular weight (Abrams et al, 2017; Guo et al, 2022; Jiang, Li, et al, 2016; Romero‐Sarmiento, Euzen, et al, 2016). To assess the proportions of different pyrolysis fractions in the shale samples, Oil‐1, Oil‐2, Oil‐3, and Oil‐4 obtained through multi‐step programmed pyrolysis were normalized and expressed as percentages (P Oil‐1 , P Oil‐2 , P Oil‐3 , and P Oil‐4 ) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-step pyrolysis divides the temperature range below 300 or 350 C into multiple heating and isothermal intervals to obtain the more easily volatilized petroleum content in shale, often referred to as the free (movable) fraction (Beti & Ring, 2019;Maende et al, 2017;Romero-Sarmiento, Euzen, et al, 2016;Romero-Sarmiento, Pillot, et al, 2016). Monitoring the pyrolysis products in different temperature intervals using thermal desorption-gas chromatography-mass spectrometry/flame ionization detection (TD-GC-MS/FID) technology confirms that the pyrolysis products in the low-temperature range have relatively smaller molecular weights (Abrams et al, 2017;Guo et al, 2022;Jiang, Li, et al, 2016;Romero-Sarmiento, Euzen, et al, 2016). However, concerns arise regarding whether the pyrolysis products from this range can accurately represent the content of free (movable) oil, given the challenge of kerogen adsorption in the low-temperature range (Abrams et al, 2017;Feng et al, 2021;Romero-Sarmiento, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shale oil and gas, as the most potential strategic replacement resources, are also hot spots for exploration and development in the global oil field in recent years [1][2][3][4][5] fracturing technology has become an essential method to develop shale oil and gas effectively [6][7][8]. Hydraulic fracturing forms artificial fractures in the shale, accompanied by the intrusion of fracturing fluids into the shale matrix.…”
Section: Introductionmentioning
confidence: 99%